1986
DOI: 10.1172/jci112428
|View full text |Cite
|
Sign up to set email alerts
|

Development of anti-human colonic mucin monoclonal antibodies. Characterization of multiple colonic mucin species.

Abstract: Structural relationships between colonic mucin species were assessed using a library of monoclonal antibodies (MAbs) directed against purified human colonic mucin (HCM). After immunization of mice with purified mucin from normal human colonic mucosa, 14% of 1,920 fusion products screened were positive for anti-HCM activity in a solid-phase assay. Patterns of selective binding by hybridomas to six discrete HCM species (I-VI) separated by DEAE-cellulose chromatography suggested the presence of both shared and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Samples of colonic and small intestinal mucosa were obtained from outbred rats (Charles River Breeding Laboratories, Wilmington, MA) and New Zealand white rabbits, after sacrifice by intraperitoneal injection of sodium pentobarbital; samples from cotton-top tamarins (S. oedipus) were obtained after anesthetization as previously described (19). All samples were promptly processed for immunofluorescent studies as described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of colonic and small intestinal mucosa were obtained from outbred rats (Charles River Breeding Laboratories, Wilmington, MA) and New Zealand white rabbits, after sacrifice by intraperitoneal injection of sodium pentobarbital; samples from cotton-top tamarins (S. oedipus) were obtained after anesthetization as previously described (19). All samples were promptly processed for immunofluorescent studies as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work in this laboratory has shown that the colonic mucosa collectively produces a complex mixture of at least six compositionally and structurally distinct mucin glycoproteins (mucin species I-VI) (9,18,19). However, the cellular basis of mucin glycoprotein heterogeneity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The development ofa library ofmonoclonal antibodies with defined, anti-mucin species specificity has provided some insight into the cellular basis of colonic mucin glycoprotein heterogeneity. Studies using indirect immunofluorescent-staining techniques suggest that there may be a previously unappreciated diversity within the large population of morphologically indistinguishable goblet cells in colonic mucosa (18,20). Staining of colonic goblet cells using monoclonal antibodies that recognize different mucin glycoprotein species indicate that particular combinations of the glycoprotein species are found in distinct subpopulations of goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in this laboratory have demonstrated the presence of substantial heterogeneity in colonic mucosal mucin glycoproteins (14)(15). At least six glycoprotein fractions initially separated by DEAEcellulose chromatography were shown to represent structurally distinct glycoprotein species (I-VI) (16)(17)(18)(19). Whereas the functional significance of this heterogeneity remains unclear, the bi-ologic relevance ofthese chromatographically distinguished species is underscored by the observation that the colonic mucosal content of one species (IV) is selectively diminished in specific association with UC.…”
Section: Introductionmentioning
confidence: 99%
“…We also used a probe corresponding to the N-terminal sequence of the rat link peptide on rat Peyer's patches and the cecal patch; again, no labeling of M cells could be detected, although goblet cells were intensely stained. Finally, we used the MAb WE9 (25), which recognizes the peptidic core of human, rat, and mouse Muc2 (32). We did not detect any signal in the FAE of rat Peyer's and cecal patches, but goblet cells from adjacent villi were labeled.…”
Section: Vol 69 2001 Apical Membrane Glycoconjugates Of Intestinal mentioning
confidence: 99%